Hellenismen i nyere forskning - Bilde, Per (Religionsvidenskabeligt Tidsskrift, 1990)
The context of the article is a research project on Hellenism initiated and sponsored by the Danish Research Council for the Humanities since 1989. In this context, a discussion of the concept of Hellenism has been going on since the project began. With the aim of widening and deepening this discussion, in this article, an attempt is made to go through a number of classical general works on the Hellenistic civilization and – in greater detail – the most important works on Hellenistic religions and on the issue of Judaism and the Hellenistic culture. However, the main theme of the treatment of recent scholarship is the question – raised recently by Reinhold Bichler (‘Hellenismus’, Geschichte und Problematik eines Epochenbegriffs, Darmstadt 1983) – whether there exists such an entity as a Hellenistic culture at all, or whether the word Hellenism should only be used as a conventional chronological term covering the period from Alexander the Great to Augustus (thus Bichler). In this article, this position is refuted, and it is argued in favour of the thesis that it is both meaningful and fruitful to use the term Hellenism with a specific cultural content, which is at the same time defined in the article.